Pannexin-1 hemichannels promote experimental colitis inflammation in a CD4+ T cell-specific manner - Mina, Pooja Rani; Macedo, Bruna de Gois; Salgado, Caio Loureiro; Leff, Chloe Liliana; Bihnam, Daniel; Borges da Silva, Henrique (Frontiers in Immunology, 2025)
BackgroundThe development of ulcerative colitis (UC) is associated with inflammatory responses driven by effector CD4+T cells, including type 3 (Th17) cells and atypical pathogenic type 2 (Th2-like) cells. UC is also linked to accumulation of neutrophils that can amplify intestinal damage. The mechanisms behind the accumulation of colitogenic CD4+ T cells are not fully understood, particularly regarding how regulators of intracellular versus extracellular metabolites can drive such responses.Main findingsHere, we found that Pannexin-1 (PANX1) hemichannels, which promote ATP export to the extracellular environment, are crucial for the development of colitis. We found that PANX1, which is upregulated in UC patients, is required for the induction of colitis in multiple experimental models. The role of PANX1 is effector T cell-specific and is correlated with the accumulation of TNF-α producing pathogenic Th2-like cells. Effector conversion of CD4+ T cells into Th2-like cells depends on PANX1. Finally, PANX1-mediated pathogenic CD4+ T cell responses correlate with the accumulation of neutrophils during colitis.ConclusionsTogether, our results suggest that PANX1 promotes colitis-associated pathogenic Th2-like responses and a possible link between these cells and colitis neutrophilia.